PENGARUH VISUAL MERCHANDISING DAN POTONGAN HARGA TERHADAP IMPULSE BUYING: (Studi pada Konsumen Matahari Plaza Medan Fair) - Sinaga, Yusuf Efendi; Marpaung, Nicholas (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to determine the effect of visual merchandising and price discounts on impulse buying (Study on Matahari Plaza Medan Fair consumers). The influence between the related variables, namely visual merchandising and price discounts, will be carried out partially and simultaneously to increase impulse buying. This study employs quantitative research with an associative methodology. Sampling utilizing the approach of purposive sampling, with 100 respondents serving as the research sample. This study's primary data were collected via Google Form questionnaires, while secondary data were obtained through a literature review. Validity test, classical assumption test, reliability test, multiple linear regression analysis, and hypothesis testing are employed as analytic methods. Results indicated that the perceived value variable (X1) partially had no effect on impulse buying (Y), whereas the discounted price variable (X2) partially had a substantial influence on impulse buying (Y). According to the coefficient of determination test, the value of R2 is 0.260, which indicates that the effect of visual merchandising and price discounts on consumers' impulse purchases at the Matahari Plaza Medan Fair is 27,5%, while the remaining 72,5% is influenced by factors that are not explained in this study.